2019
DOI: 10.1093/jjco/hyz104
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pemetrexed plus cisplatin as first-line chemotherapy in advanced malignant peritoneal mesothelioma

Abstract: Background Malignant peritoneal mesothelioma (MPeM) is a rare cancer for which no standard systemic chemotherapy has been established. While cisplatin plus pemetrexed, the standard treatment for malignant pleural mesothelioma (MPlM), is usually used for MPeM, its efficacy remains unclear. Methods We retrospectively reviewed the medical charts of MPeM patients who had received cisplatin plus pemetrexed as first-line chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The e cacy of pemetrexed in combination with cisplatin in patients with MPeM has been reported in two studies, with response rates of 20% and 29.8%, respectively, and a median survival of 13.1 months in one study and not reached in the other [6] , [7]. In our retrospective study, the combination of cisplatin and pemetrexed for MPeM was effective, and the median progression-free survival (PFS) and overall survival (OS) were 7.1 and 15.4 months, respectively [8]. Replacing cisplatin with carboplatin has been shown to result in similar treatment e cacy [7] , [9].…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The e cacy of pemetrexed in combination with cisplatin in patients with MPeM has been reported in two studies, with response rates of 20% and 29.8%, respectively, and a median survival of 13.1 months in one study and not reached in the other [6] , [7]. In our retrospective study, the combination of cisplatin and pemetrexed for MPeM was effective, and the median progression-free survival (PFS) and overall survival (OS) were 7.1 and 15.4 months, respectively [8]. Replacing cisplatin with carboplatin has been shown to result in similar treatment e cacy [7] , [9].…”
Section: Introductionmentioning
confidence: 56%
“…This study was conducted as an expanded analysis of the e cacy of rst-line platinum-based chemotherapy following our previous study [8]. Furthermore, we also evaluated a second-line treatment and explored the prognostic factors in patients who received second-line treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In another study on the efficacy and safety of pemetrexed plus cisplatin as first-line chemotherapy in advanced malignant peritoneal mesothelioma, Nagata et al reported among hematological toxicities, Incidence of grade 3/4 leukopenia, neutropenia, anemia and thrombocytopenia were 21%, 17%, 14% and 3%, respectively [ 28 ]. Moreover, in a study for assessment of efficacy and safety of pemetrexed maintenance chemotherapy for advanced NSCLC in a real-world setting conducted in 2021, authors have mentioned grade 1/2 hematological toxicities as the most commonly reported toxicities with leukopenia in 35.2% and neutropenia in 23.9% of patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is often combined with surgery to treat MPM, which can be delivered in the form of heated intraperitoneal chemotherapy (HIPEC). Nagata Y et al found that cisplatin plus pemetrexed showed consistent e cacy with MPM [34], which can be recommended as rst-line treatment for unresectable MPM. Yan et al reported the median survival of 56 months for 372 patients who received HIPEC and 23 months for those who did not (P = 0.…”
Section: Discussionmentioning
confidence: 99%